Integrated Energy Audit for Workshop and Learning Systems - Aminatus Sa’diyah; Mohamad Hakam; Evi Nafiatus; Mey Rohma Dhani; Muhammad Anis Mustaghfirin; George Endri Kusuma; Muchammad Nidhor Fairuza (Newinera Publisher, 2025)
The south workshop building is utilized for practical activities involving high machine loads, while the learning building is designated for theoretical activities. In order to optimize energy efficiency, a comprehensive audit of the lighting and electrical systems. A comparative case study approach was utilized for the analysis. A comprehensive audit of the lighting and electrical systems in both environments was conducted. An Internet of Things (IoT) monitoring system was utilized to track power consumption in both buildings. Illumination measurements were obtained using a lux meter and were subsequently compared with the Standard of Lighting (SNI) and the Permenaker standards. The average level of illumination was measured at 128.4 lux in the southern workshop and below 150 lux in some classrooms of the learning building. An electrical analysis revealed that the dominant load in the south workshop was from welding machines (10.9 kVA), whereas in the learning building, it was from the cooling system and electronic equipment. A comparative analysis of the south workshop building and the learning building reveals that both structures possess considerable potential for energy conservation. Recommendations for improvement include upgrading the lighting system and implementing an IoT system to support specific electrical load management for each building.